Protecting Consumer Interests under Competition Law and International Perspective: Examining Consumer Protection and Competition Law: An International Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This topic will be dealing with the various issues relating to consumer protection under the competition law in India, and the position in various other countries. Whether consumer protection is the ultimate goal of competition law or the enforcement of competition law leads to the protection of consumer interests, as a consequence. What is the stand taken by the competition of India, regarding cases involving consumer grievances, what is the standard of consumer welfare required to be taken into consideration while dealing with competition issues, and to what extent is protection accorded to consumers under other legislations. Whether there is a need for a unified redressal agency for cases regarding competition and consumer protection, or an amendment to the competition act for ensuring better protection to consumers.